The Influence Of The Creative Economy On Suistainable Sharia Economics Growth In Indonesia : Sharia Financial Perspectives - Rahman, Diba Nur; K, Kamilah; Syahriza, Rahmi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research aims to analyze the influence of the Creative Economy on Economic Growth and sustainable sharia finance in Indonesia. This research uses a quantitative approach with a verification type of research. Secondary data was obtained through the Ministry of Tourism and Creative Economy (KEMENPAREKRAF), namely creative economy data and the Central Statistics Agency (BPS), namely export data and economic growth and suistainable sharia finance in Indonesia. The population in this research is the entire growth data for each variable from 2014 to 2023. The samples used in this research are the creative economy, exports and economic growth and suistainable sharia finance during the 2014-2023 period, each of which consists of 40 samples taken from annual data in the form of time series data using data interpolation. Other data was obtained through observation and literature study. The analysis technique used is multiple linear regression. The research results show that Creative Economy Fashion, Creative Economy Crafts, and Creative Economy Culinary have no effect on Economic Growth and Sustainable Sharia Finance in Indonesia through exports as an intervening variable. So it can be concluded that indirectly, the leading subsectors of the creative economy, namely fashion, crafts and culinary, through exports are not able to influence economic growth and suistainable sharia finance.